Convective drying kinetics of osmotically pretreated papaya cubes - João P. de L. Ferreira; Deise S. de Castro; Inacia dos S. Moreira; Wilton P. da Silva; Rossana M. F. de Figueirêdo; Alexandre J. de M. Queiroz (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study assessed the fitting of mathematical models to the convective drying kinetics of osmotically pre-dehydrated papaya cubes. Papaya cubes were subjected to osmotic dehydration in sucrose solutions at 40 and 50 ºBrix, at temperatures of 50 and 60 ºC, followed by complementary convective drying in forced air circulation oven under three temperatures (50, 60 and 70 °C) and constant air velocity of 1.0 m s-1. Ten thin-layer drying mathematical models were fitted to the experimental data. The increase in air temperature and the decrease in osmotic solution concentration resulted in increased water removal rate. Based on the statistical indices, the Two Terms model was the one that best described the drying kinetics of the samples for all evaluated conditions. The effective diffusion coefficients increased with the elevation of air temperature, ranging from 1.766 x 10-10 to 3.910 x 10-6 m2 s-1, whereas the convective mass transfer coefficients ranged from 3.910 x 10-7 to 1.201 x 10-6 m s-1 with Biot number from 0.001 to 12.500.